QUEUE ANALYSIS SYSTEM IN PT. BANK MANDIRI (PERSERO) TBK. BRANCH MELAWAI JAKARTA, SOUTH JAKARTA - Aulia Ashari; Linda Wahyu Widianti, Skom, MMsi (Jurnal Sistem Informasi, 2009)
This study aims to estimate the performance of queuing systems, to determine the cause of the queuing system performance barriers, and to find solutions to overcome obstacles in the queue on transaction processing performance at PT.  Branch Bank Melawai, South Jakarta. In analyzing the performance of the queue on the transaction process as well as the problem and the solution the author uses the model of a queuing system or a dual path Quiuery Multiple Channel System. Use of this queuing system models based on the number of tellers at Bank Mandiri Branch Melawai, South Jakarta is one of five people with stage lines of service. The outcome of the double lane queuing system model is obtained that the work rush hour Teller is at 14:00 to 15:00 hours, at which period the average time that customers wait as much as two people. Therefore, according to author queuing system performance problems at Bank Mandiri Branch Melawai is on the large number of customers who queue to get service, and the  cause of this problem are due to imbalance in the capacity in which the amount is not in accordance with the capacity Teller customers who come in busy periods. Reducing the number of customers who queue up in the process of increasing the number of transactions conducted through Teller. Author's calculations results by adding one person Teller obtained decrease in the number of customers waiting in line as much as a person (being a person). However, according to the author in regulating the addition amount of Teller, PT. Bank Mandiri Branch Melawai need to consider the busyness of the work unit level. In order for the operational performance of the Bank Mandiri Branch Melawai not disturbed the overall transaction process can be optimized and then the addition of a teller can be taken from the work unit that is not too busy.